Design in crisis : new worlds, philosophies and practices - Fry, Tony.; Nocek, A. J. (Abingdon, Oxon : Routledge, 2021)
"This book is an essential contribution to the transdisciplinary field of critical design studies. The essays in this collection locate design at the center of a series of interrelated planetary crises, from climate change, nuclear war, and racial and geopolitical violence to education, computational culture, and the loss of the commons. In doing so, the essays propose a range of needed interventions in order to transform design itself and its role within the shifting realities of a planetary crisis. It challenges the widely popular view that design can contribute to solving world problems by exposing how this attitude only intensifies the problems we currently face. In this way, the essays critique the dominant modes of framing the meaning and scope of design as a largely Anglo-European "problem-solving" practice. By drawing on post-development theory, decolonial theory, black studies, continental philosophy, science and technology studies and more, the contributions envision a critical and speculative practice that problematizes both its engagement with planet and itself. The essays in this collection will appeal to design theorists and practitioners alike, but also to scholars and students generally concerned with how the past and future of design is implicated in the unfolding complexity of ecological devastation, racial and political violence, coloniality, technological futures, and the brutality of modern western culture generally"--
Designing as a future praxis for the healing of the web of life / Arturo Escobar -- Designing in the world of the naturalized artificial / Clive Dilnot -- Unlearning and relearning design / Madina Tlostanova.
Includes bibliographical references and index.
Keywords: Design -- Philosophy; Crises (Philosophy)